Community of Urban Arisan Mothers: Promoting Joy and Mental Health in Urban Residents - Junardi Harahap; Rita Destiwati (Universitas Andalas, 2024)
This study focuses on looking at the cultural dimension, promoting and spreading joy, and creating mental health in urban communities. The specific aim is that if mental health problems and stress are not handled properly, it can have a bad impact, especially when seen in urban communities, which are very busy and have very complex problems, and one of the things that is done to strengthen this is by holding social gathering activities. In the cultural dimension, of course, this is very interesting, as seen from the activities in urban areas carried out by mothers who provide and promote mental health in urban communities. This research is qualitative, carried out through observations and interviews with 18 informants. The results of this research found that the practice of social gathering is one of the solutions and interventions for maternal mental health in urban areas, and urban mothers can improve their quality of life. The meetings held provided solutions for their lives and improved their quality of life. This research contributes to the development of knowledge in the realm of health anthropology regarding the strategies and solutions used by mothers in urban areas to achieve good mental health.